Effectiveness of differentiated learning in mathematics: insights from elementary school students - Rijal, Akmal; Aswarliansyah, Aswarliansyah; Waluyo, Budi (Intelektual Pustaka Media Utama, 2025)
This study looked at the effectiveness of differentiated learning in enhancing students' mathematical outcomes by incorporating varied content, processes, and products. Employing a mixed-methods experimental design, the research hypothesized that differentiated instruction significantly influences students' performance in mathematics exams. The differentiation strategy involved altering the level of support in group discussions (process), adjusting the material's difficulty (content), and modifying the nature of student tasks (products). The participants comprised sixty-five fifth-grade students from public elementary schools. Data collection utilized interviews, document analysis, observations, and test questions, with the t-test and paired sample t-tests comparing pretest and post-test scores to assess the impact. The findings revealed that differentiation in content, process, and product significantly enhances student mathematical achievements, thereby supporting the initial hypothesis. This suggests that teachers should tailor instruction by varying the structure, support, and autonomy of task completion and product creation. Future research should expand the application of content, process, and product differentiation to a broader sample, including different mathematical materials and extending to high schools, to further validate these results and explore additional educational contexts.